Europium doping-induced stability and quantum confinement effect in ZnO quantum well wires QWW: Electronic structure calculation and material structural investigation in terms of band-gap shift - Yahşi, Uğur; Yumak, Ayşe; Petkova,Petya; Boubaker,Karemt Ben Mahmoud (My University, 2016)
ZnO quantum well wires QWW have been grown on glass substrates by an inexpensive, simplified and enhanced spray pyrolysis technique, at 460°C and using Zn(CH3COO)2·2H2O as main precursor. Consecutively, the as-grown wires have been gradually doped by Europium within hexa-hydrated chlorinated Europium EuCl3·6H2O (ACROS, 99.0% purity) with different europium-doping levels (0, 0.5 and 1.0 at%). The effects of Eu-doping on the structural and optical properties of the QWW were investigated. Results reflect that accuracy of control can be achieved on functional performance by adjusting doping extent. Two-dimensional self-consistent calculations of the electronic structure within the Brillouin zone, along with Lattice Compatibility Theory analyses results show excellent agreement with the experimental results. © 2015 Elsevier B.V.
Keywords: Band-gap shift; Doping thin films; Europium; Morphology; Optical properties; Quantum well wires QWW; ZnO